Controllable Syntheses, Structure Identifications, and Property Explorations of Self-Intercalated 2D Transition Metal Chalcogenides - Cheng, Yujin; Quan, Wenzhi; Wang, Jialong; Peng, You; Zhou, Tong; Ding, Haoxuan; Zhang, Yanfeng (Small methods, 2025)
2D transition metal dichalcogenides (2D TMDCs) have attracted intensive interest in physics and materials science-related fields, due to their exotic properties (e.g., superconductivity, charge density wave (CDW) phase transition, magnetism, electrocatalytic property). Intercalation of native metal atoms in the layered 2D TMDCs (e.g., from VS to V S by V intercalation) can afford new stoichiometric ratios, phase states, and thus rich properties. This review hereby summarizes the recent progress in the controllable syntheses, structure characterizations, and property explorations of self-intercalated 2D transition metal chalcogenides (TMCs), with the metal elements focusing on group-V, VI, and VIII metals. The self-intercalation-related synthetic strategies will be introduced via chemical vapor deposition (CVD) and molecule beam epitaxy (MBE), especially by tuning the chemical potentials of intercalated metal elements, growth promoters, substrates, etc. Additionally, the structure/phase identifications of the self-intercalated 2D TMCs through various characterization techniques will be overviewed. More significantly, the intriguing properties in such 2D TMCs will be thoroughly discussed, such as the thickness- or composition-dependent magnetism, CDW phase transition, electrocatalytic property, etc. Finally, challenges and prospects are proposed for developing new self-intercalated 2D materials and their heterostructures and exploring their unique properties and applications.